Systematic variation in the temperature dependence of bacterial carbon use efficiency - Smith, Thomas P.; Clegg, Tom; Bell, Thomas; Pawar, Samrāt; Bardgett, Richard (Ecology letters, 2021)
Carbon use efficiency (CUE) is a key characteristic of microbial physiology and underlies community‐level responses to changing environments. Yet, we currently lack general empirical insights into variation in microbial CUE at the level of individual taxa. Here, through experiments with 29 strains of environmentally isolated bacteria, we find that bacterial CUE typically responds either positively to temperature, or has no discernible response, within biologically meaningful temperature ranges. Using a global data synthesis, we show that these results are generalisable across most culturable groups of bacteria. This variation in the thermal responses of bacterial CUE is taxonomically structured, and stems from the fact that relative to respiration rates, bacterial population growth rates typically respond more strongly to temperature, and are also subject to weaker evolutionary constraints. Our results provide new insights into microbial physiology, and a basis for more accurately modelling the effects of thermal fluctuations on complex microbial communities. Carbon use efficiency (CUE) is a key characteristic of microbial physiology and underlies community‐level responses to changing environments, however we currently lack an understanding of how CUE varies with temperature. Combining new empirical data with those of a data synthesis, we find that bacterial CUE typically responds either positively to temperature, or has no discernible response, within biologically meaningful temperature ranges.